High Temperature Effects on Black Carbon Filled NRSBR Elastomer Behavior - REZIG, Naima; BELAHCENE, Tassadit; MAY, Abdelghani; ABERKANE, Méziane (University of Eloued جامعة الوادي, 2018)
In the present work, the effect of high temperatures on an Natural Rubber/Styrene Butadiene Rubber (NR/SBR) mixture behavior was studied. Thus, uni-axial tensile tests and Differential Scanning Calorimetry (DSC) analyzes on virgin and aged specimens at different temperatures were realized. Later, Scanning Electron Microscopy (SEM) micrographs were made to examine fracture facies and thermal aging influence on the elastomer surface morphology. The results obtained showed that the mechanical properties of the material deteriorate when the thermal aging is more severe. Indeed, high temperature led to rapid degradation of the studied NR/SBR mixture. This loss of elasticity is due to the increase in thermal stability, resulting from a decrease in chains’ mobility. Moreover, DSC analyzes revealed that the glass transition temperature tended to increase with aging time and temperature. Changes in mechanical properties seem to be in good agreement with the SEM obtained micrographs, where structural alteration is recorded under high temperatures. In conclusion, mechanical and structural behavior of the studied elastomer was significantly altered by high temperature.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Thermal aging, Filled elastomer, Mechanical properties, Glass transition temperatures.